Parallel, cascaded, interactive processing of words during sentence reading. - Wen, Yun; Snell, Joshua; Grainger, Jonathan (Cognition, 2019)
Single words are easier to identify in a briefly presented syntactically correct word sequence compared with a scrambled version of the same set of words: a sentence superiority effect. Interactive-activation models of sentence comprehension can account for this phenomenon by implementing parallel processing of word identities. The cascaded and interactive nature of such processing allows sentence-level structures to influence on-going word processing. Alternatively, prior observations of a sentence superiority effect in post-cued word-in-phrase identification might be due to the sophisticated guessing of word identities on the basis of partial information about the target word and the surrounding context. Here, for the first time, we used electrophysiological recordings to plot the time-course of the sentence superiority effect. According to an interactive-activation account of this phenomenon, the effect should be visible in the N400 component, thought to reflect the mapping of word identities onto higher-level semantic and syntactic representations. Such evidence for changes in highly automatized linguistic processing is not predicted by a sophisticated guessing account. Our results revealed a robust and widespread sentence-superiority effect on the N400 component that onsets around 270 ms post-sentence onset, thus lending support to the interactive-activation account.